Macroeconomics of growth cycles and financial instability - Ferri, Piero (Cheltenham Edward Elgar Publishing Ltd.)
Summary from British Library catalogue: In light of the recent economic crisis and in keeping with Hyman Minsky's analysis of financial instability, this book considers the important interaction between cycles and growth, via the interplay between demand, supply and real-world financial issues. Piero Ferri presents a macroeconomic study of a monetary production economy within a dynamic paradigm, where instability phenomena and inhibitive policy measures interact, and where the forces that self-regulate markets cannot prevent the occurrence of instability problems. Underpinning this paradigm is the idea that such volatility is the result of endogenous forces; shocks can trigger instability but cannot explain its persistence. As endogenous instability has multiple causes and mechanisms of transmission, the author adopts various perspectives - both analytical and by means of simulation - in order to explore and characterize the phenomenon of growth cycles and instability. This challenging book will prove a thought-provoking read for students and scholars of macroeconomics, heterodox economics, labour markets and money, finance and banking.
Introduction --
Part I: The Background
1. Dynamics in the medium run --
2. Financial instability --
3. Macroeconomics, uncertainty and the fallacies of composition --
4. Heterogeneity and the status of macroeconomics --
Part II: The Markets --
5. The Nature of the labor market --
6. The Role of imperfect competition --
7. Policies versus self-adjustment Part III: Endogenous dynamics --
8. A Dynamic macro model --
9. Uncertainty, expectations and learning --
10. Inflation, deflation and the phillips curve --
Part IV: Growth cycles, income share and the financial instability hypothesis --
11. A Growth cycle model --
12. The Role of labor share --
13. Towards a stochastic switching --
Part V: Concluding remarks --
14. Lessons --
15. The Task ahead.
Includes bibliographical references (p. 174-189) and index.
Keywords: Business cycles; MACROECONOMICS; BUSINESS CYCLES; GROWTH